SUPPORTIVE SUPERVISION AS A TECHNOLOGY OF IMPROVING THE QUALITY OF HOSPITAL CARE DELIVERY - Svetlana A. Mukhortova; Tatiana V. Kulichenko; Leyla S. Namazova-Baranova; Svetlana G. Piskunova; Elena A. Besedina; Dmytrij V. Prometnoy (Union of pediatricians of Russia, 2017)
Improving the quality of medical care is a priority in countries with developed and developing health care system. There are various approaches to improve the quality and safety of patient's care, as well as various strategies to encourage hospitals to achieve this goal. The purpose of the presented literature review was to analyze existing experience of the implementation of technology of supportive supervision in health care facilities to improve the quality of hospital care delivery. The data sources for publication were obtained from the following medical databases: PubMed, Cochrane Library, Medscape, e-library, and books on the topic of the review written by experts. The article discusses the results of the research studies demonstrating the successes and failures of supportive supervision technology application. Implementation of supportive supervision in medical facilities based on generalized experience of different countries is a promising direction in improving the quality of medical care delivery. This technology opens up opportunities to improve skills and work quality of the staff at pediatric hospitals in the Russian Federation.